2021
DOI: 10.1007/s12325-021-01911-7
|View full text |Cite
|
Sign up to set email alerts
|

Galcanezumab in Patients with Multiple Previous Migraine Preventive Medication Category Failures: Results from the Open-Label Period of the CONQUER Trial

Abstract: Introduction:Results from the open-label extension of the phase 3b CONQUER trial are presented to evaluate the effectiveness and safety of galcanezumab, a monoclonal antibody targeting calcitonin gene-related peptide, for up to 6 months in patients with multiple prior migraine preventive treatment failures. Methods: Patients were 18-75 years old with episodic or chronic migraine and 2-4 standardof-care migraine preventive medication category failures. After 3 months of randomized treatment with galcanezumab (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Notably, pooled subgroup analysis assessing the safety profile of fremanezumab in participants aged ≥ 60 years reported comparable findings with the overall pooled population [ 33 ]. Furthermore, the CONQUER study, which enrolled patients aged 18‒75 years, found no clinically significant safety findings for AEs, laboratory analytes, vital signs, or ECGs in the subgroup of patients aged 65‒75 years treated with galcanezumab, albeit the sample size was low ( N = 29) [ 34 ]. While this provides preliminary evidence that use of CGRP mAbs may be safe in individuals beyond 65 years, real-life studies in larger populations of older individuals are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, pooled subgroup analysis assessing the safety profile of fremanezumab in participants aged ≥ 60 years reported comparable findings with the overall pooled population [ 33 ]. Furthermore, the CONQUER study, which enrolled patients aged 18‒75 years, found no clinically significant safety findings for AEs, laboratory analytes, vital signs, or ECGs in the subgroup of patients aged 65‒75 years treated with galcanezumab, albeit the sample size was low ( N = 29) [ 34 ]. While this provides preliminary evidence that use of CGRP mAbs may be safe in individuals beyond 65 years, real-life studies in larger populations of older individuals are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the DBTP, 462 patients with episodic or chronic migraine were randomly assigned to placebo or galcanezumab 120 mg (with a loading dose of 240 mg) (25). Of the 451 patients who completed the DBTP, all but two patients entered the OLE and 96% completed the study (26). The previous placebo group started the OLE with a blinded loading dose of 240 mg and reported a reduction of −3.9 MMD in the first OLE month (26).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 451 patients who completed the DBTP, all but two patients entered the OLE and 96% completed the study (26). The previous placebo group started the OLE with a blinded loading dose of 240 mg and reported a reduction of −3.9 MMD in the first OLE month (26). Both groups reported thereafter similar reductions with 120 mg galcanezumab monthly (26).…”
Section: Resultsmentioning
confidence: 99%
“…When stratifying by EM and CM, galcanezumab achieved a MMD reduction of − 2.88 and − 5.90, respectively. OLE data of CONQUER reported galcanezumab achieved a MMD reduction of − 5.6 in the galcanezumab continuous group, and − 5.2 in those who switched from placebo to galcanezumab [ 56 ].…”
Section: Calcitonin Gene-related Peptide (Cgrp)-targeted Mabsmentioning
confidence: 99%